Strategi Digitalisasi UMKM Es Krim Duriberika Pada Era Society 5.0 Untuk Meningkatkan Daya Saing Usaha Berkelanjutan - Lisa Rahmania Dewi; Ana Husnul Hotimah; Romida Arta Uli S; Bagas Lutfi Maulana; Ahmad Rifki (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the digitalization strategy implemented by um cream MSMEs in facing the Society 5.0 era in order to increase business competitiveness sustainably. Digitalization has become a crucial need for MSMEs to expand market access, strengthen branding, and improve operational efficiency. This study uses a qualitative method that combines structured interview techniques, in-depth interviews, and MSME-based observations. Based on the interview results, it shows that Duriberika ice cream MSMEs have utilized social media as their main promotional tool. Based on the results of observations and interviews that have been conducted, Duriberika ice cream MSMEs utilize various digital channels such as WhatsApp and instagram to promote products, increase market reach, and build interactions with customers. With the use of appropriate technology, continuous product innovation, and a commitment to continue following the development of digital trends. Duriberika ice cream MSMEs are expected to be able to survive and develop as a highly competitive student business in the Society 5.0 era.